2013
DOI: 10.1002/rcs.1507
|View full text |Cite
|
Sign up to set email alerts
|

Single‐site robotic cholecystectomy: efficiency and cost analysis

Abstract: Robotic single-site cholecystectomy is a safe, cost-effective alternative to single-incision laparoscopic cholecystectomy in a robot-existing model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(39 citation statements)
references
References 25 publications
(42 reference statements)
2
36
0
1
Order By: Relevance
“…Surgeon reputation is therefore a key but under-recognized factor driving episodes of surgical care (18), probably second only to the effort expended by the surgeon during the procedure. One of the major factors limiting the number of cases performed by a surgeon in a day is the duration of conventional open or laparoscopic procedures spent in ergonomically uncomfortable positions (19). Vidovszky et al suggested that the ergonomics of robotic surgery diminishes fatigue and reduces surgeon injuries relative to long hours holding laparoscopic instruments in unsupported positions (20).…”
Section: The Surgeon Value Propositionmentioning
confidence: 99%
See 3 more Smart Citations
“…Surgeon reputation is therefore a key but under-recognized factor driving episodes of surgical care (18), probably second only to the effort expended by the surgeon during the procedure. One of the major factors limiting the number of cases performed by a surgeon in a day is the duration of conventional open or laparoscopic procedures spent in ergonomically uncomfortable positions (19). Vidovszky et al suggested that the ergonomics of robotic surgery diminishes fatigue and reduces surgeon injuries relative to long hours holding laparoscopic instruments in unsupported positions (20).…”
Section: The Surgeon Value Propositionmentioning
confidence: 99%
“…Buzad and colleagues compared robotic vs. laparoscopic cholecystectomies at a single institution and analyzed operating room times, case volume, and instrument costs excluding amortization of the robot, utilities, and yearly maintenance (19). While operative times and instrument costs were similar ($1,325 versus $1,145), the robotic technique allowed that facility to perform a higher number of cholecystectomies per operative day.…”
Section: Rcmentioning
confidence: 99%
See 2 more Smart Citations
“…Buzad и соавт. (2013) не выявили статисти-чески значимых различий в оперативном времени между робот-ассистированной ЛХЭ и ТЛХЭ -84,6 и 85,5 мин соответственно (p=0,8737), потери крови и осложнения были минимальными, материальные затраты эквивалентны [60].…”
Section: рис 4 система Endosamurai для управления ин-струментами с unclassified